Overbuilding and development cascades under irrational expectations - Lv, Xiu-Mei; Fan, Gang-Zhi (International Journal of Strategic Property Management, 2015)
The recent sluggish recovery in the U.S. house market has further motivated our research interests in overbuilding in real estate markets. Our model is an extension to Grenadier’s (1996), who emphasizes rational investment decisions possibly leading to oversupply in real estate markets, by further allowing for the important implication of irrational expectation for the strategic interaction amongst competing investors. In this model, two market participants are asymmetric because one of them is allowed to have heterogeneous expectations about the growth and volatility of demand shocks. Unlike most of previous studies that only simply think of this phenomenon as a result of irrationality, our model further finds that irrational investors’ value-maximizing investment choices matter in understanding the strategic interaction of investment decisions in real estate markets, therefore providing additional insights into overbuilding and other puzzling phenomena in real estate markets.